2011
DOI: 10.1200/jco.2010.33.4441
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blocker Use Is Associated With Improved Relapse-Free Survival in Patients With Triple-Negative Breast Cancer

Abstract: A B S T R A C T PurposeTo examine the association between beta-blocker (BB) intake, pathologic complete response (pCR) rates, and survival outcomes in patients with breast cancer treated with neoadjuvant chemotherapy. Patients and MethodsWe retrospectively reviewed 1,413 patients with breast cancer who received neoadjuvant chemotherapy between 1995 and 2007. Patients taking BBs at the start of neoadjuvant therapy were compared with patients with no BB intake. Rates of pCR between the groups were compared using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
330
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(361 citation statements)
references
References 46 publications
14
330
3
1
Order By: Relevance
“…Several retrospective clinical studies also provide evidence that b-blocker usage is associated with improved relapsefree survival in patients with breast cancer (Powe et al 2010, Barron et al 2011, Melhem-Bertrandt et al 2011. Our results reveal that the b2-AR-mediated signaling pathway plays critical roles in manipulating tumor angiogenesis by integrating multiple mechanisms.…”
Section: Discussionsupporting
confidence: 62%
“…Several retrospective clinical studies also provide evidence that b-blocker usage is associated with improved relapsefree survival in patients with breast cancer (Powe et al 2010, Barron et al 2011, Melhem-Bertrandt et al 2011. Our results reveal that the b2-AR-mediated signaling pathway plays critical roles in manipulating tumor angiogenesis by integrating multiple mechanisms.…”
Section: Discussionsupporting
confidence: 62%
“…The aim of these studies is the identification of novel target molecules and target pathways that efficiently block tumor cell migration, thereby impairing or slowing down metastasis formation. An example for such an effort might be β-blockers, which have been shown to inhibit the metastatic spreading of breast cancer cells in vitro and in vivo 36 and which have been associated with an improved relapse-free survival in patients with triple-negative breast cancer cells 37 . We have recently demonstrated that hybrid cells, which derived from spontaneous fusion events between a human breast epithelial cell line and a human breast cancer cell line, but not the parental cells, responded to the chemokine CCL21 with an increased migratory activity 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Although these drugs do not seem to affect breast cancer incidence and tumorigenesis, a beneficial effect in terms of less advanced disease at diagnosis and lower cancer-specific mortality was observed in patients who have taken propranolol 1 year before diagnosis. 19 Longer disease-free survival 18 and reduced metastasis development and tumor recurrence were also observed in several studies, 17,20 whereas some studies did not measure a significant effect of b-blockers on breast cancer recurrence or survival. 66,67 In these latter studies, the majority of patients were taking b1AR-selective antagonists, which is different from all preclinical studies mostly based on effects via the b2AR and the use of b1/b2 non-selective antagonists.…”
Section: Stress B-blockers and Survival In Patients With Breast Cancermentioning
confidence: 91%
“…11,13,14 In addition, major depression is a frequent but under-recognized and under-treated condition among breast cancer patients. 15,16 The use of b-blockers, on the other hand, has been associated with prolonged survival in women treated for breast cancer, [17][18][19][20] as well as in patients affected with prostate, 21,22 lung, 23 ovarian 24 and cutaneous melanoma. 25,26 A commonality among these studies is that the conditions and drugs involved affect the sympathetic nervous system (SNS), whose activity is stimulated by chronic stress and depression and inhibited by b-blockers.…”
Section: Neuroendocrine Factors and Bone Metastasismentioning
confidence: 99%